PENGARUH LAMA PAJANAN LOGAM BERAT KADMIUM (Cd) TERHADAP KADAR KALSIUM (Ca) DAN KADAR FOSFAT PADA TULANG TIKUS PUTIH (Rattus novergicus) - Erliyanti, Emmi; Mahreda, Emmy Sri; Triawanti, Triawanti; Suhartono, Eko (EnviroScienteae, 2015)
This study aimed to analyze the long exposure to Cadmium (Cd) on the levels of calcium and phosphate bone white mice. This study uses a white rat bone exposed and unexposed Cd were 24 male rats were divided into 4 groups for 0, 2, 4 and 6 weeks. After the surgery and then measured levels of calcium and phosphate bone white mice. The results showed that there were significant differences in the levels of Ca between control and treatment groups. White rat bone Ca levels decreased respectively 118,067 mg/gram of bone; 87,267 mg/gram of bone; 39,667 mg/gram of bone and 13,067 mg/gram bone at weeks 0, 2, 4 and 6. The results of statistical tests performed by Kruskal-Wallis (p=0.000; p<0.05), it is stated that long exposure to Cd can significantly reduce levels of Ca in the bones of mice. This happens due to a decrease in absorption in the intestine Cd Cd compete with, so that the levels of Ca in bones decreased. In addition the research also showed levels of phosphate bone consecutive weeks 0, 2, 4 and 6 is equal to 335,583 mg/L; 258,583 mg/L; 251,833 mg/L and 208,667 mg/L. Results of statistical tests performed by Kruskal-Wallis (p=0.116; p>0.05), which means that exposure to Cd can not lower phosphate levels significantly due to the reciprocal relationship between Ca and P which resulted in secretion of parathyroid hormone so the bone does not release phosphate in the number of great. Thus concluded that exposure to heavy metals cadmium (Cd) for 6 weeks can reduce bone calcium white mice, but have not been able to reduce levels of phosphate bone white mice significantly.